PRIMEIROS SOCORROS NO AMBIENTE ESCOLAR: DISPOSITIVO PARA MONITORAMENTO DOS SINAIS VITAIS DE CRIANÇAS - Silva, Giovane Souza da (2021)
Introduction: First aid procedures are those performed to save lives in situations of medical emergencies, offering immediate care to maintain vital functions until specialized care is available and improving the prognosis. Knowledge on first aid is disseminated little among the general population and is nearly always the exclusive domain of health professionals. Justification: Accidents are the main cause of death among children between one and 14 years of age in Brazil. Annually, approximately 3.7 thousand children in this age group die and another 113 thousand are hospitalized due to these causes in the country. The school setting is one of the places in which urgent and emergency situations can occur, as children spend a large part of their day in this environment. It is therefore fundamental for teachers to feel prepared, confident, and equipped to act in cases of necessity. Objectives: 1) Develop a device for monitoring the vital signs of children connected to other equipment that could be used by schoolteachers, parents, and other caregivers and activated in the case of changes in the vital signs; 2) perform a literature review on the knowledge of schoolteachers regarding first aid; 3) measure the self-confidence of primary schoolteachers regarding the initial management of health problems before and after training in first aid conducted by a specialist in the field. Methods: The following steps were considered in the design of the product: (1) contract and consulting agreement with the Innovation Agency of Universidade Franciscana; (2) survey of similar products in the market; (3) conceptual modeling of the device; (4) establishment of the development protocol with validation through an effectivity test with a sample of monitored children. Validation will be performed through an effectiveness test involving a sample of children monitored by a private emergency service in the city of Santa Maria, Rio Grande do Sul, Brazil. For the literature review, an integrative review was performed with searches conducted in the Biblioteca Virtual em Saúde (BVS [Virtual Health Library]) and MEDLINE/PubMed. The descriptors were “Primeiros Socorros” and “Professores Escolares” in the BVS database and “First Aid” and “School Teachers” in MEDLINE/PubMed, which were combined using the Boolean operator AND. Data collection was performed between October and November of 2020. Regarding the scientific research, an intervention study was performed. The intervention consisted of training in first aid offered by a specialist to primary schoolteachers in the municipal system of the city of São Sepé, Rio Grande do Sul, Brazil. A validated visual analogue scale was used to measure the degree of self-confidence of the teachers regarding first aid in the school setting prior to training, immediately after training, and six months after the end of the intervention. Data analysis involved descriptive statistics, the paired t-test, and the calculation of the effect size. Results: The product – entitled “device for monitoring the vital signs of children” – is currently in the prototype construction phase and in search of partnerships with businesses that have interest in placing this innovation on the market. The patent claim has been registered with the Instituto Nacional de Propriedade Intelectual (INPI [National Institute of Intellectual Property]). For the integrative review, 17 studies met the eligibility criteria. Four co-related empirical categories were established: the low level of knowledge of schoolteachers regarding first aid; the need for urgent actions to train teachers; the training activities performed proved quite effective at preparing teachers for first 15 aid situations; the importance of continual training. During the intervention, 109 teachers were trained in the five districts of the city, totaling 12 schools. Mean overall confidence of the teachers was 30.19 (SD: 14.38) before training, 58.59 (SD: 14.74) after training and 59.57 (SD: 9.57) after 6 months (p value <0,05). On all questions, an increase in the level of confidence of teachers was found immediately after training and this increase was maintained at the six-month evaluation. Effect size of overall level of self-confidence was 2.07 after intervention and 2.14 after six months. Final considerations: The lack of knowledge on first aid among schoolteachers underscores the need for continual training to increase their self-confidence in situations of necessity in the school setting and demonstrates the importance of equipment to assist teachers in monitoring the children. Technical product: Assets of Intellectual Property, characterized as an invention patent (technological advance). The “device for monitoring the vital signs of children” could be used by teachers, parents, and other caregivers, offering greater security in the monitoring of these children and preventing adverse health outcomes. If such conditions are recognized and children are promptly sent for necessary care, the repercussions to their health would be less harmful.